Conclusions and future developments - Carruba, Valerio [UNESP]; Smirnov, Evgeny; Oszkiewicz, Dagmara (Elsevier, 2024)
In this chapter, we aim to revise the content presented in this book, classify the status of ML applied to small bodies as a research field, using metrics already in use for other astronomical areas where ML has been applied, and present some possible future trends and worthy subjects of exploration for applications of AI and ML to Solar System small bodies.
Keywords: Databases; Minor planets, asteroids: general; Minor planets, asteroids: individual